The effect of a 12-week strength and conditioning programme on youth golf performance - Coughlan, D.; Taylor, M. J. D.; Wayland, W.; Brooks, D.; Jackson, J. (International Journal of Golf Science, 2020)
Physical preparation in golf is well-recognised as an essential component of high level performance, but research into youth golfers is limited. The purpose of this study was to determine the effect of a once weekly strength and conditioning session on physical performance over 12-weeks. Thirty-nine male golfers aged 11-17 years (age: 13.54 ± 1.10 yrs, mass: 59.68 ± 13.10 kg, handicap: 10.26 ± 4.67 strokes) were assigned to either an intervention or control group. The control group did not participate in structured training whereas the intervention group received supervised resistance training. Outcome measures were clubhead speed (CHS), ball speed (BS), countermovement jump (CMJ) predicted power and modified pull-ups. Magnitude based inferences and confidence intervals were used to assess the response between groups based on pre-determined threshold values. The intervention demonstrated likely increases in CHS (4.25mph; CI90 1.79 to 6.71), possible increases in ball speed (4.09mph; CI90 0.78 to 7.40), likely increases in CMJ predicted power (308.35W; CI90 176.97 to 439.73). There were only trivial differences in modified pull-ups. This study highlights the potentially positive impact a once weekly strength and conditioning programme can have on physical performance and CHS in youth golfers, and is therefore recommended in this population.